THE IMPACT OF THE US-CHINA TRADE WAR ON THE STABILITY OF THE RUPIAH EXCHANGE RATE: A SHARIAH HEADING APPROACH - Parlindungan; Mirzah Ikmaliyah; Heru Kurniawan (Universitas Efarina, 2023)
The trade war between the United States and China has created significant global economic uncertainty, affecting exchange rate stability in developing countries, including that of the Indonesian Rupiah. This study aims to analyze the impact of the US-China trade war on the stability of the Rupiah exchange rate and to explore the application of the Sharia hedging approach as a solution to manage exchange rate fluctuation risks. Using a qualitative method based on a literature review, this study found that in early 2025, the Rupiah exchange rate depreciated by 8% against the US Dollar due to global trade tensions and a domestic current account deficit. The widely used conventional hedging strategies have proven effective but are not in line with Islamic economic principles. On the other hand, Sharia-compliant hedging, such as wa’ad, salam, and murabahah mu’ajjal, offers a more ethical, inclusive, and Sharia-compliant solution. These instruments can mitigate exchange rate risk without involving elements of speculation, gharar, or riba. The implementation of Sharia hedging requires close collaboration between Islamic banks, business actors, and regulators to ensure its effective and appropriate application. This research concludes that the Shariah hedging approach can strengthen the stability of the Rupiah exchange rate while also supporting the principles of Shariah economics.